Complement and Microglia in the Neuropathogenesis of HIV Infection: Pro- and Anti-Inflammatory Aspects - Speth, Cornelia; Rambach, Gunter; Sopper, Sieghart (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2009)
Viral penetration into the central nervous system (CNS) is an early event in the course of human immunodeficiency virus (HIV) pathogenesis and occurs in the vast majority of the infected individuals. Consequences are diverse symptoms of neurological dysfunction in a substantial proportion of patients, as well as the establishment of a lifelong viral reservoir. The severity of symptoms ranges from subclinical alterations in motor and cognitive functions termed HIV neurocognitive impairment (HNCI) to full blown HIV-associated dementia (HAD) in late stages of AIDS. The interaction of HIV with the cerebral immunity is an important aspect of the pathogenesis and has not yet been elucidated in detail. The blood-brain barrier strictly limits the access of peripheral immune elements, thus emphasising the role of the local innate immunity. The two central players of the antimicrobial campaign in the brain are complement and microglia. The complement system represents a fast-acting soluble cascade with a broad variety of antiviral effector mechanisms whereas microglia are the most potent cellular immune elements in the CNS. Both orchestrate a network of innate immune reactions that aim to limit HIV spreading. On the other hand, however, the inflammatory processes may exceed any reasonable limit and develop a dynamic that makes them contribute to the virus-induced neurological damage and dysfunctions. In the present article we describe profit, limitations and danger of the pro-inflammatory activities executed by complement and microglia in the HIV-infected brain. Furthermore we speculate about putative benefits of pro-inflammatory therapies to support the antiviral immune reaction, as well as of anti-inflammatory therapeutic approaches to avoid excessive inflammation and subsequent neurological lesions.
Keywords: innate immunity